Halobacteriovorax vibrionivorans sp. nov., a novel prokaryotic predator isolated from coastal seawater of China. Issue 12 (9th September 2019) - Ye, Xiao-Sheng; Chen, Ming-Xia; Li, He-Yang; He, Xiao-Yu; Zhao, Yan
Abstract : Three prokaryotic predator strains, BL9 T, BL10 and BL28, were isolated with Vibrio alginolyticus from coastal seawater of PR China. Cells of the strains were Gram-negative, vibrioid-shaped and motile with a single sheathed flagellum (25–28 nm wide). Cells were around 0.3×0.5–1.0 µm in size. The three strains were obligate predators that exhibited a biphasic life cycle: a free-swimming attack phase and an intraperiplasmic growth phase within the prey. Bdelloplasts were formed. NaCl was required for growth. Optimum growth occurred at 37 °C, with 2–4 % (w/v) NaCl and at pH 7.0–8.0. The results of phylogenetic analyses based on 16S rRNA gene sequences indicated that the three strains shared 99.9 % similarity to each other, were affiliated with the genus Halobacteriovorax in the class Oligoflexia, and represented the same new species. Strain BL9 T (=MCCC 1K03527 T =JCM 32962 T ) was designated as the type strain. Genome sequencing of strain BL9 T revealed a genome size of 3.14 Mb and a G+C content of 35.8 mol%. The estimated digital DNA–DNA hybridization (dDDH) values and the whole genome average nucleotide identity (gANI) values between the genome of strain BL9 T and those of Bdellovibrionales and Bacteriovoracales were 12.5–19 and 63.49–76.15 %, respectively. On the basis of life cycle features, results of physiological analyses, gANI data and dDDH data, strain BL9 T represents a new species within the genus Halobacteriovorax, for which the name Halobacteriovorax vibrionivorans sp. nov. is proposed.